UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUI PENGGUNAAN MEDIA POHON LITERASI DALAM PEMBELAJARAN PENDIDIKAN PANCASILA PADA MATERI HAK DAN KEWAJIBAN SEBAGAI ANGGOTA KELUARGA DAN WARGA SEKOLAH DI KELAS IV SD NEGERI BALFAI (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve the learning outcomes of fourth-grade students at SD Negeri Balfai in the Pancasila Education subject, particularly on the topic of rights and obligations as family and school members, through the use of the literacy tree learning media. This research employed Classroom Action Research (CAR) consisting of planning, action, observation, and reflection stages. The subjects consisted of 25 students. Data were collected through teacher and student activity observations, learning outcome tests, and documentation. The findings of the study indicate that the use of the literacy tree media successfully increased students’ engagement and participation during learning activities, as well as improved their understanding of the subject matter. Prior to the implementation of the action, student learning mastery was only 40%. This increased to 44% in the first cycle, yet had not met the required mastery criteria. After revisions and improvements implemented in the second cycle, learning mastery significantly increased, reaching more than 80% in accordance with the classical mastery standard. The improvement in learning outcomes was supported by an increase in both teacher and student activity scores, which progressed from the “sufficient” category in the first cycle to the “good” and “very good” categories in the second cycle. Therefore, it can be concluded that the literacy tree learning media is effective in improving learning outcomes in Pancasila Education among fourth-grade students at SD Negeri Balfai.